Evaluation of antidepressant activity of tramadol in comparison with imipramine in Swiss albino mice - Bonda, Chiranjeevi; Pawar, Sudhir; Lokhande, Jaisen (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The aim of the study was to evaluate the antidepressant effect of opioid analgesic tramadol using forced swim test and tail suspension test models. Methods: The antidepressant effect was assessed by recording the immobility time in Forced swim test (FST) and Tail suspension test (TST). The mice were randomly divided into five groups. Mice belonging to group I was given normal saline (0.1ml/kg) which acted as control. Group II received imipramine (15mg/kg) considered as the standard drug tramadol was given in graded dose (10, 20 and 40 mg/kg) to mice of groups III, IV, V respectively. All drugs were administered intraperitoneally for seven successive days; test was done on 7th day. Results: Tramadol and Imipramine showed antidepressant activity when compared to control. There is dose dependent increase in antidepressant activity of tramadol. The antidepressant activity of imipramine was significantly (P<0.05) more than tramadol at dose 10 and 20 mg/kg but antidepressant activity with tramadol 40mg/kg was comparable to imipramine treated mice. Conclusions: The results of this study indicated the presence of antidepressant activity of tramadol at 40mg/kg.